Driver state examination—Treading new paths. (June 2016) - Wascher, Edmund; Getzmann, Stephan; Karthaus, Melanie
Highlights: We investigate states of mental fatigue in a monotonous driving simulation experiment. We analyze performance, EEG oscillation and synchronization, and evoked potentials. Alpha power reflects attentional withdrawal due to monotony rather than fatigue. EEG synchronization and evoked potentials are more valid indicator of mental fatigue. Abstract: A large proportion of crashes in road driving can be attributed to driver fatigue. Several types of fatigue are discussed, comprising sleep-related fatigue, active task-related fatigue (as a consequence of workload in demanding driving situations) as well as passive task-related fatigue (as related to monotonous driving situations). The present study investigated actual states of fatigue in a monotonous driving situation, using EEG measures and a long-lasting driving simulation experiment, in which drivers had to keep the vehicle on track by compensating crosswind of different strength. Performance data and electrophysiological correlates of mental fatigue (EEG Alpha and Theta power, Inter Trial Coherence (ITC), and auditory event-related potentials to short sound stimuli) were analyzed. Driving errors and driving lane variability increased with time on task and with increasing crosswind. The posterior Alpha and Theta power also increased with time on task, but decreased with stronger crosswind. The P3a to sound stimuli decreased with time on task when the crosswind was weak, but remained stable when the crosswind was strong. The analysis of ITC revealed less frontal Alpha and Theta band synchronization with time on task, but no effect of crosswind. The results suggest that Alpha power in monotonous driving situations reflects boredom or attentional withdrawal due to monotony rather than the decline of processing abilities as a consequence of high mental effort. A more valid indicator of declining mental resources with increasing time on task seems to be provided by brain oscillatory synchronization measures and event-related activity.